Muhammad Helmi Faizal Pengaruh Spiritual Leadership Terhadap Workplace Spirituality Dan Organization Citizenship Behavior Serta Dampaknya Terhadap Performance Pada Personel Kepolisian Daerah Sumatera Utara: Pengaruh Spiritual Leadership Terhadap Workplace Spirituality Dan Organization Citizenship Behavior Serta Dampaknya Terhadap Performance Pada Personel Kepolisian Daerah Sumatera Utara - Faizal, Muhammad (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to examine and analyze the effect of Spiritual Leadership on personnel Performance through Workplace Spirituality and Organizational Citizenship Behavior, directly or indirectly. The approach used in this research is a causal approach. The population in this study were all police personnel at the North Sumatra Regional Police Directorate of Special Criminal Investigation (Ditreskrimsus). The sample in this study used the slovin formula sample, totaling 69 police personnel at the North Sumatra Regional Police Directorate of Special Criminal Investigation (Ditreskrimsus). Data collection techniques in this study used documentation, observation, and questionnaire techniques. Data analysis techniques in this study used a quantitative approach using statistical analysis using Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study indicate that Spiritual Leadership, Workplace Spirituality and Organizational Citizenship Behavior have a direct effect on employee performance, Spiritual Leadership has a significant effect on Workplace Spirituality, and Spiritual Leadership, Workplace Spirituality has a significant effect on Organization Citizenship Behavior and indirectly Spiritual Leadership has a significant effect on personnel performance through Workplace Spirituality and Organizational Citizenship Behavior of police personnel at the North Sumatra Regional Police Directorate of Special Criminal Investigation (Ditreskrimsus)